Do two heads think better than one? Collaborative Learning in academia - Kaalvik, Hilde (Septentrio Conference Series, 2020)
Introduction: This study examines how 13 bachelor students on Faculty of Medicine and Health Sciences experience collaborative learning on campus at NTNU. My purpose was to find out how students reflect upon collaborative learning face to face on Campus, especially according to learning outcome. The findings are based on empirical data. I investigate how they handle collaborative learning, problems they meet and choices they make while collaborating. My findings will be presented in five different main themes. Method: I analyzed three focus group interviews with 13 students using SDI-model and Nvivo12. I focused on the student’s descriptions and reflections of collaborative learning and learning outcome. Results: The students have a lot of reflections about collaborative learning in akademia. The analysis resulted in five different themes named ‘the teacher’s role’, ‘the role of friction’, ‘the role of being prepared’, ‘consciousness’ and ‘meaning making’. Conclusion: The study implies that to achieve desired effect of learning from collaborative learning the universities should continue to encourage active learning strategies. Especially important to succeed is the teacher’s role in scaffolding, the role of friction and the role of being prepared. The role of consciousness and meaning-making is also important in constructing and creating knowledge. This presentation main message is to show the role of collaborative learning on Campus according to why universities should continue to focus on a change in practice which include active learning strategies to succeed teaching.